Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis presenting to the emergency department with status epilepticus. Issue 5 (September 2014) - Nolan, Brodie; Plenk, Katharina; Carr, David
ABSTRACT: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is a recently described and underdiagnosed entity that typically affects young, previously healthy individuals. Patients usually present in phases, which may include refractory seizures, psychosis, unresponsiveness, and autonomic instability. The diagnosis of anti-NMDAR encephalitis is challenging; however, prompt diagnosis and early treatment can lead to complete recovery. The incidence of anti-NMDAR encephalitis may be as high as four times that of encephalitis from herpes simplex, varicella-zoster, and West Nile viruses; however, it remains an underrecognized disorder. Early initiation of immunotherapy in anti-NMDAR encephalitis has been found to improve patient outcomes. Because of this, emergency physicians must be vigilant and consider this diagnosis in patients with altered mental status in whom a toxicologic or other etiology is not suspected. Early consideration of this diagnosis can facilitate urgent neurology consultation and prevent diagnostic delays arising from psychiatric referrals. It is essential to consider this diagnosis in suspicious emergency department presentations, particularly young patients who present with altered mental status, psychosis, or new-onset seizure activity when other obvious causes are ruled out. Emergency physicians should discuss the possibility of empirical intravenous immunoglobulin administration with neurology consultants if anti-NMDAR encephalitis is suspected. We describe the case of a 20-year-old man with anti-NMDAR encephalitis who presented to the emergency department with status epilepticus.